2021
DOI: 10.1016/j.jns.2021.117587
|View full text |Cite
|
Sign up to set email alerts
|

An implantable device to treat multiple sclerosis: A discrete choice experiment on patient preferences in three European countries

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…An overview of the case studies and their DCE designs can be found in Table 1. [30][31][32] Attributes and levels were selected based on literature reviews, focus groups, and interviews; these are presented in Table 2. The first case study concerned the treatment preferences of patients with multiple sclerosis (MS) in The Netherlands, France, and the UK.…”
Section: Case Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…An overview of the case studies and their DCE designs can be found in Table 1. [30][31][32] Attributes and levels were selected based on literature reviews, focus groups, and interviews; these are presented in Table 2. The first case study concerned the treatment preferences of patients with multiple sclerosis (MS) in The Netherlands, France, and the UK.…”
Section: Case Studiesmentioning
confidence: 99%
“…The first case study concerned the treatment preferences of patients with multiple sclerosis (MS) in The Netherlands, France, and the UK. 30 Inclusion criteria were the following: aged 18 years or older, diagnosis of MS, and living in one of these 3 European countries. Respondents were recruited online via the commercial survey sampling company Survey Engine (N = 753).…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation